Challenges and Limitations of Moodle LMS in Handling Large-Scale Projects: West-African Universities Lecturers’ Perspective - Olugbade, Damola; Ojo, Olayinka Anthony; Tolorunleke, Adebayo Emmanuel (Tauladan Fathimah Azzahra, 2023)
This study investigates the perceptions of lecturers from 11 West African universities about the effectiveness of the Moodle Learning Management System (LMS) in managing large-scale projects. Employing a cross-sectional survey design, data was collected through an online questionnaire encompassing demographic information and evaluations of Moodle LMS. A convenience sampling approach yielded responses from 51 lecturers, and data analysis involved descriptive statistics, t-tests, and ANOVA. The findings indicate that lecturers generally view Moodle LMS positively, citing its user-friendly interface and capacity for fostering collaboration and student engagement. However, areas for enhancement, particularly resource adequacy, were identified. Gender-based disparities were observed, with male lecturers exhibiting a more positive perception of Moodle’s capabilities. Satisfaction levels varied across features, with communication tools, assignment management, and gradebook/assessment tools receiving higher ratings. Overall, lecturers expressed high satisfaction levels, a willingness to recommend Moodle LMS to peers, and contentment with available technical support and training opportunities. Notably, no significant variations in perception emerged among lecturers from different universities using Moodle LMS. These findings offer valuable insights for optimizing the use of Moodle LMS in managing large-scale projects within West African universities, affirming its consistent impact across diverse institutional settings.